Self-reporting scaffolds for in situ monitoring for regenerative medicine and tissue engineering applications - Ahmed, Shehnaz (2018)
This thesis describes the development and utilisation of a self-reporting scaffold to improve current monitoring methods of the cellular microenvironment. In vitro tissue models hold a lot of promise for regenerative medicine and tissue engineering. However, many models lack the ability to non-invasively monitor in situ cellular responses in a physiologically relevant environment. By development of electrospun self-reporting scaffolds and incorporation of flow culture conditions, this limitation can be overcome. Electrospun matrices have been shown to mimic the structural architecture of the native extracellular matrix, whilst flow conditions have been shown to regulate cellular processes, and enhance mass transport and nutrient exchange throughout polymeric scaffolds. Here we show the development of optically transparent self-reporting electrospun scaffolds that incorporate ratiometric pH-sensitive nanosensors and respond to biological and mechanical cues of the native extracellular matrix through exposure to shear stress. Optically transparent self-reporting scaffolds were fabricated by directly electrospinning pH responsive, ratiometric nanosensors within a gelatin biopolymer matrix. The sensors consist of a porous polyacrylamide matrix which encapsulates pH-sensitive fluorophores that exhibit an additive fluorescent response across the full physiological range between pH 3-8, and a pH-insensitive reference fluorophore. The self-reporting scaffold was able to support cell growth whilst being able to simultaneously monitor local pH changes in real time. A Quasi-Vivo® bioreactor system was also used to generate a flow of cell culture medium and expose cell-seeded scaffolds to a continual shear stress. This novel diagnostic scaffold and the use of flow conditions can help simulate enhance the understanding of in vitro conditions, and generate advanced simulations in vivo to facilitate tissue engineering and regenerative medicine applications.